RETRACTED: Elementary school students’ mathematical connection in problem-posing activities - Mohammad Archi Maulyda; Awal Nur Kholifatur Rosyidah; Vivi Rachmatul Hidayati (Universitas Hamzanwadi, 2022)
This article has been retracted at the request of the editor-in-chief of Jurnal Elemen. After publication of “Elementary school students’ mathematical connection in problem-posing activities” in Jurnal Elemen, Volume 8, Issue 1 (January 2022), DOI: https:/doi.org/10.29408/jel.v8i1.4364. It was found that the data used had been previously published and belonged to another author who was not included in the authorship. The data were used without the consent of the rightful data owner. The authors have acknowledged this issue and requested the withdrawal of the article. The Editorial Board determined that this constitutes a violation of publication ethics and the Retraction and Withdrawal of Manuscript Policy of Jurnal Elemen (https://e-journal.hamzanwadi.ac.id/index.php/jel/raw). The article has therefore been retracted to maintain the integrity of the scholarly record and will remain online, clearly marked as Retracted.